Online Food Marketing in Supporting Food Security Based on the Perspective of Urban Consumers in Riau Province - Fanny Septya; Yulia Andriani; Anne Mudya Yolanda (Perum BULOG, 2023)
Changes in people’s behavior in shopping for food needs from offline to online are rife in urban communities, especially in Pekanbaru and Dumai cities. This study aimed to identify consumer characteristics and gaps in online food purchase activities and analyze the mapping of consumer perceptions of online food marketing in support of regional food security. The research used a qualitative and quantitative descriptive approach with a nonmetric multidimensional scaling (MDS) analysis tool. The data collection method used a survey purposively selected 140. The results showed that the majority of consumers who purchased food online were women, with the majority of respondents being 26–35 years old, having a high school education and household income of Rp3,000,000.00–4,999,000.00 and having two dependents in the family. The monthly online food expenditure averaged Rp300,000.00 twice the monthly buying frequency. Food types often purchased online were frozen food and ready-made food. Based on the analysis of perception mapping, the availability of food products in the online market all the time, affordable food prices, transaction facilities, improvement of food distribution systems, and the use of varied and diverse foods selections were the determining indicators for online food marketing in supporting regional food security according to the perspective of urban consumers.